How Slow Rock Weathering Balances Nutrient Loss During Fast Forest Floor Turnover in Montane, Temperate Forest Ecosystems - Uhlig, David; von Blanckenburg, Friedhelm (Frontiers in Earth Science, 2019)
Mineral nutrient cycling between trees and the forest floor is key to forest ecosystem nutrition. However, in sloping, well-drained landscapes the forest floor experiences permanent nutrient loss in particulate form by plant litter erosion and as solute after plant litter decomposition, solubilisation and export. To prevent nutrient deficit, a replenishing mechanism must be in operation that we suggest to be sourced in the subsoil and the weathering zone beneath it, provided that atmospheric input is insufficient. To explore such a mechanism, we quantified deep (up to 20 m depth) weathering and mineral nutrient cycling in two montane, temperate forest ecosystems in Southern Germany: Black Forest (CON) and Bavarian Forest (MIT). From measurements of the inventories, turnover times, and fluxes of macronutrients (K, Ca, Mg, P) we found evidence for a fast, shallow `organic nutrient cycle´, and a slow, deep `geogenic nutrient pathway´. We found that the finite nutrient pool size of the forest floor persists for a few years only. Despite this loss, foliar nutrient concentrations in Picea abies and Fagus sylvatica do not indicate deficiency. We infer that ultimately the biologically available fraction in the deep regolith (CON: 3 - 7 m, MIT: 3 - 17 m) balances nutrient loss from the forest floor and is also decisive for the level of the forest trees’ mineral nutrient stoichiometry. Intriguingly, although the nutrient supply fluxes from chemical weathering at CON are twice those of MIT, nutrient uptake fluxes into trees do not differ. The organic nutrient cycle apparently regulates its efficiency to cater for differences in its replenishment by the deep geogenic nutrient pathway, and thereby ensures long-term forest ecosystem nutrition.